Facile Fabrication of Superhydrophobic Polymer Membranes with Hierarchical Structure for Efficient Oil/Water Separation - Kim, Da Seul; Kang, Jeongmin; Jung, Jae Yeong; Hwang, Minsik; Seo, Soonmin; Kim, Ju Hyung (Fibers and Polymers, 2022)
Superhydrophobic polymer membranes provide highly promising methods for efficient oil/water separation because of their cost effectiveness, and environmental friendliness. A variety of polymers have been widely used for the membrane fabrication, among which polyurethane acrylate (PUA) presents strong advantages of excellent mechanical strength with high deformability and chemical stability. In this study, we present a facile and rapid method for the fabrication of PUA-based superhydrophobic membranes with hierarchical structure, enabling efficient oil/water separation. For this work, PUA membranes with uniform pores were prepared via soft lithography, on which silica nanoparticles were deposited. The nanoparticles were preferentially functionalized with a silane coupling agent to lower the surface energy, and then spray-coated onto the PUA membrane supports to spontaneously form the hierarchical structure possessing superhydrophobic properties and excellent wettability to oil. Efficient oil/water separation was successfully demonstrated using a mixture of hexane and water with a separation efficiency of ∼97 %, and the membranes could withstand a high pressure of ∼2.0 kPa. We anticipate that these results will significantly contribute not only to the fabrication of superhydrophobic membranes with uniform pores but also the development of more diversified polymer-based membranes and separators leading to a wide range of applications.
Keywords: Environmental friendliness; Facile fabrication; Hierarchical structures; Oil/water separation; Polymer membrane; Polyurethane/acrylate; Silica nanoparticles; Superhydrophobic; Surface Functionalization; Uniform pore; Hydrophobicity; Oil/water separation; Polymer membranes; Silica nanoparticles; Surface functionalization